Eliminating the trust factor - Cann, Henk van (Technical Centre for Agricultural and Rural Cooperation, 2018)
Henk van Cann is co-founder of Blockchain Workspace, an organisation based in Amsterdam, the Netherlands that provides training on the blockchain to make the technology understandable to a broad audience. Henk spoke to ICT Update about the need to educate people about the blockchain before they start using it and judging it, and why trust is one of the key drivers for moving away from centralised systems and towards blockchain technology.